Personnal, occupational and geographical satisfaction in the staff of a state university in Costa Rica: effect of sex, marital status, age and educatio - Arce Espinoza, Lourdes (2015)
Satisfaction is determined by a set of external and internal factors of the individual, experiences, culture and the environment; it changes with goals and achievements. Here I analyze the results of an online survey of 1000 institutional email users from a public university in Costa Rica. Men are more satis ed with life in general and single, widowed or divorced people are less satis ed than those living with a partner. The greatest satisfaction is associated with tenure, being over 31 years old and having a high academic degree. Overall satisfaction is medium-high which is consistent with other local studies.